Analisis Pengaruh Kinerja Keuangan, Manajemen Resiko dan Manajemen Modal Kerjaterhadap Return Saham (Studi Kasus pada Perusahaan Telekomonikasi yang Listing di BEI Tahun 2016-2020) - Muryati Muryati; Akhmadi Akhmadi (CITRA EKONOMI, 2021)
This study aims to determine the effect of the financial performance of telecommunications companies listed on the Stock Exchange with the proxy Debt to equity ratio, return on investment, current ratio and total assets turn over then risk management using interest rates and working capital management using cash conversion cycle on stock returns. year 2016-2020. The population and sample are telecommunications companies listed on the Indonesia Stock Exchange and meet the research requirements, totaling 4 companies. Data collection is done by downloading the financial statements of each company on the IDX website. Analysis of the data in this study using SPPS version 20. Data testing techniques include normality assumption test, multiple regression analysis and partial test. In analyzing the effect of the variables DER, ROI, CR, TATO, ir and CCC using multiple linear regression. The results showed that the Debt to Equity Ratio (DER) had an effect on stock returns with a significant value of 0.008, Return on Investment (ROI) had a significant effect on stock returns with a significant value of 0.002. And Total Asset Turn Over (TATO) has an effect on stock returns with a significance value of 0.015. Meanwhile, Current Ratio (CR), interest rate (IR), and Cash Conversion Cycle (CCC) have no effect on stock returns with a significance value of 0.289; 0.312; 0.675. All independent variables simultaneously affect the shares in telecommunications companies.